PROPOSED CO-CREATION STRATEGY FOR COMMUNITY BASED MARKETING AND BOARD GAME COMMUNITY MONETISATION (CASE STUDY MAHAVIRA.STUDIO IN JAKARTA INDONESIA) (The Indonesian Journal of Business Administration, 2019)
Board game internationally is in emerging trend and Indonesia is still catching up to the trend, Indonesia board game market is still very small compared to European market, or even Japanese and Singapore market. MAHAVIRA.studio as a board game publisher have a mission to accelerate awareness of the board game in Indonesia. Traditional board game in Indonesia is already known by many of the Indonesian such as Mancala, Monopoly, and UNO, contradict with modern board game Indonesia still have long way to reach the maturity of the board game market. A regional board game community became the quick solution for the still tiny market compared to other hobbies. Board game publisher with their designer is already emerging from major city in Indonesia with higher risk of failure because of the information and awareness to board game in Indonesia is still low.The main problem in board game industry awareness in Indonesia is an accesbility of the board game to the masses and board game community in Indonesia with proper way of intergrating regional based community. Board game industry itself is need a leverage to grow, and increasing the quality of the industry in Indonesia. One option to increasing the awareness of the board game industry is to collaborate within industry and cooperate with other industry.MAHAVIRA.studio using co-creation, collaboration, and cooperation with many board game stakeholder in Indonesia, analyzing the resource advantage of co-creation, and determine the correct market audience with STP and marketing mix analysis. Researcher using analysis tools mentioned to draw conclusion and developing strategy to raise awareness of board game with co-creation of system, collaboration inside board game publisher, and making alternate monetization cooperation plan.Keywords: board game, Indonesia, market awareness, community development, monetization system development, co-creation, collaboration, cooperation